Positive adaptation of HPA axis function in women during 44 weeks of infantry-based military training. (December 2019) - Gifford, R.M.; O'Leary, T.J.; Double, R.L.; Wardle, S.L.; Wilson, K.; Boyle, L.D.; Homer, N.Z.M.; Kirschbaum, C.; Greeves, J.P.; Woods, D.R.; Reynolds, R.M.
Highlights: Women demonstrated no maladaptive HPA-axis effects to 11-month arduous military training. The training was stressful; mood and resilience scores decreased throughout. Saliva cortisol increased initially, then demonstrated habituation. Hair cortisol increased throughout training. Fasting cortisol decreased and stimulated cortisol increased during training. Abstract: Background: Basic military training (BMT) is a useful model of prolonged exposure to multiple stressors. 8–12 week BMT is associated with perturbations in the hypothalamic-pituitary-adrenal (HPA) axis which could predispose recruits to injury and psychological strain. However, characterisations of HPA axis adaptations during BMT have not been comprehensive and most studies included few if any women. Methods: We studied women undertaking an arduous, 44-week BMT programme in the UK. Anxiety, depression and resilience questionnaires, average hair cortisol concentration (HCC), morning and evening saliva cortisol and morning plasma cortisol were assessed at regular intervals throughout. A 1-h dynamic cortisol response to 1 μg adrenocorticotrophic hormone-1-24 was performed during weeks 1 and 29. Results: Fifty-three women (aged 24 ± 2.5 years) completed the study. Questionnaires demonstrated increased depression and reduced resilience during training (F 6.93 and F 7.24, respectively, both p < 0.001). HCC increased from 3 months before training to the final 3 months of training (median (IQR) 9.63 (5.38, 16.26) versus 11.56 (6.2, 22.45) pg/mg, p = 0.003). Morning saliva cortisol increased during the first 7 weeks of training (0.44 ± 0.23 versus 0.59 ± 0.24 μg/dl p < 0.001) and decreased thereafter, with no difference between the first and final weeks (0.44 ± 0.23 versus 0.38 ± 0.21 μg/dl, p = 0.2). Evening saliva cortisol did not change. Fasting cortisol decreased during training (beginning, mid and end-training concentrations: 701 ± 134, 671 ± 158 and 561 ± 177 nmol/l, respectively, p < 0.001). Afternoon basal cortisol increased during training while there was a trend towards increased peak stimulated cortisol (177 ± 92 versus 259 ± 13 nmol/l, p = 0.003, and 589 ± 164 versus 656 ± 135, p = 0.058, respectively). Discussion: These results suggest a normal stress response in early training was followed quickly by habituation, despite psychological and physical stress evidenced by questionnaire scores and HCC, respectively. There was no evidence of HPA axis maladaptation. These observations are reassuring for women undertaking arduous employment.